Abscisic acid interplays with PPARγ receptors and ameliorates diabetes-induced cognitive deficits in rats - Razieh Kooshki; Akbar Anaeigoudari; Mehdi Abbasnejad; Khadijeh Askari-Zahabi; Saeed Esmaeili-Mahani (Mashhad University of Medical Sciences, 2021)
Objective: This study intended to evaluate if central administration of abscisic acid (ABA) alone or in combination with GW9662, a peroxisome proliferator-activated receptor γ (PPAR-γ) antagonist, could modulate learning and memory as well as hippocampal synaptic plasticity in a rat model of streptozotocin (STZ)-induced diabetes. Materials and Methods: Intraperitoneal injection of STZ (65 mg/kg) was used to induce diabetes. Diabetic rats were than treated with intracerebroventricular (i.c.v.) administration of ABA (10, 15 and 20 µg/rat), GW9662 (3 µg/rat) or GW9662 (3 µg/rat) plus ABA (20 µg/rat).Animals' spatial and passive avoidance learning and memory performances were assessed by Morris water maze (MWM) and shuttle box tasks, respectively. Further, in vivo electrophysiological field recordings were assessed in the CA1 region. Results: STZ diabetic rats showed diminished learning and memory in both MWM and shuttle box tasks.  The STZ-induced memory deficits were attenuated by central infusion of ABA (10 and 20 µg/rat). Besides, STZ injection impaired long-term potentiation induction in CA1 neurons that was attenuated by ABA at 20 μg/rat. Central administration of GW9662 (3 µg/rat) alone did not modify STZ-induced spatial and passive avoidance learning and memory performances of rats. Further, GW9662 prevented ABA capacity to restore learning and memory in behavioral and electrophysiology trials. Conclusion: Altogether, ABA ameliorates cognitive deficits in rats via activation of PPAR-γ receptor in diabetic rats.